Entrepreneurship and Economic Freedom: Do Objective and Subjective Data Reflect the Same Tendencies? - Burak Erkut (Entrepreneurial Business and Economics Review, 2016)
Objective: The research question is whether the same tendencies on entrepreneurship, innovation and economic freedom can be captured by subjective (Global Entrepreneurship Monitor) and objective (Index of Economic Freedom) data – and to which extent one can classify countries by different data sources in a theoretical framework based on the national competitiveness of each country.